Development and Validation of an Advanced Actuator Line Model for Wind Turbines - Papi, Francesco; Melani, Pier Francesco; Xie, Shengbai; Perrone, Carmelo; Scienza, Pietro; Balduzzi, Francesco; Bianchini, Alessandro (E3S web of conferences, 2021)
As wind turbine technology proceeds towards the development of more advanced and complex machines, modelling tools with fidelity higher than the ubiquitous Blade Element Momentum (BEM) method are needed. Among them, the Actuator Line Method (ALM) stands out in terms of accuracy and computational cost. Moving from this background, an advanced ALM method has been developed within the commercial solver CONVERGE®. As elements of novelty, this tool features a Lagrangian method for sampling the local inflow velocity and a piece-wise smearing function for the force projection process. Various sub-models for both Horizontal Axis Wind Turbines (HAWTs) (e.g. the Shen tip loss correction) and Vertical Axis Wind Turbines (VAWTs) (e.g. the MIT dynamic stall model) has also been included. Aim of the research is to address the new challenges posed by modern machines. HAWTs are in fact getting larger and larger, shifting the research focus on the interaction of increasingly deformable blades with the atmosphere at the micro- and mesoscale level. VAWTs on the other hand, whose popularity has arisen in the last years, thanks to their advantages in non-conventional applications, e.g. floating offshore installations, are extremely complex machines to study, due to their inherently unsteady aerodynamics. The approach has been validated on selected test cases, i.e. the DTU 10MW turbine and a real 2-blade H-rotor, for which both high-fidelity CFD and experimental data are available.